TABLE CLINICOPATHOLOGIC AND SURVIVAL IN PATIENTS WITH BREAST SARCOMA - Díaz, Juan (2015)
Objectives: To identify clinical-pathological picture and 5 year survival rate of patients with breast sarcoma. Material and methods: We review retrospectively the files of 14 patients with primary soft tissue sarcoma of the breast treated at Belen and Regional Teaching Hospitals, Trujillo, Perú, between 1966 and 1996. Results: Mean age was 46 ± 15,8 years (range 17 to 74 years). The mean time of history was 18 months (range 3 to 48 months). The most frequent symptoms were tumor (100%) and pain (28%,) and the presence of ulceration was a common sign (21%,). All patients had unilateral lesions and the right breast was the site most commonly affected (57%). The mean tumor size was of 13 ± 7,9 cm (range 2 to 30 cm). Most patients presented T2 lesions (n=12) and no lymph node or distant metastases at admission. The predominant histologic types were malignant phyllodes tumor (42,9%), stromal sarcoma (28,6%) and fibrosarcoma (21,4%,). The surgical procedures used were simple mastectomy (n=6), simple mastectomy with lower axillary dissection (n=3), Halsted’s mastectomy (n=2), tumorectomy (n=2) and quadrantectomy (n=1). Three patients (21%) with malignant phyllodes tumor of low histologic grade developed local recurrence at mean time of 23±14, month after surgical treatment. The 5 year survival rate in the total series was 61%. Conclusión: Breast sarcoma is a rare neoplasia and its diagnosis ¡s obtained with surgical biopsy prior to the definitive surgical treatment.